Mindfulness and Productivity Workspace Design Factors for Work from Home - Moch. Restu Subagya; Wiryono Raharjo (CV. Gio Architect, 2026)
The economic crisis of 2024 led many businesses to use online freelancers, and some of them work from home (WFH). Despite its seeming convenience, WFH has the potential to cause issues related to productivity, physical health, and mental health, primarily due to poorly designed workspaces. Therefore, having a workspace designed to trigger mindfulness can be a solution. This research aims to investigate the workspace design factors related to mindfulness and productivity in the WFH context. The factors and issues data obtained in literature reviews were then analyzed and formulated into a table to show their direct and indirect relationship with workspace design. The study's findings show that the direct relationship is dominated by physical comfort in the physical work environment and mindfulness environment factors. Meanwhile, the indirect relationship is dominated by household characteristics, individual factors, and psychological comfort in the physical work environment. Additional testing is required to support the research findings.